Deprived of the Islamic Financing and Lack of Inclusion of Muslim Populated States in India: An Empirical Study - Mansha Rafiq; Khaliq Ahmad; Abideen Adeyemi Adewale (UIN Siber Syekh Nurjati Cirebon, 2025)
Introduction: Financing is the backbone of economic growth. It serves as the lifeblood of any business. However, any financial exclusion, especially Islamic financing exclusion driven by a socio-economic and political purpose to deprive of certain segment of society due to suspicion of terrorism or suppressions by state, makes a difference. In fact, these are banking services and financing facilities originally intended to provide socio-economic benefits to the overall citizenry and the general public, but they have certain limitations in policy prescriptions. It is crucial to make the availability of financial services the leading and primary objective of the public policy, and not discriminate on the basis of ones’ social status, caste, religio, or wealth. In March 2005, the former Prime Minister Dr. Manmohan Singh, an architect of modern Indian economic revilism who passed away recently, appointed a high-level committee to prepare a report on the social, economic, and educational status of Indian Muslims, under the chairmanship of Justice Rajendra Sachar. The Sachar Report is considered the most valuable document that delves into the social, economic, and educational status of the Muslim community of India. The findings of this report revealed a shocking testimony to decades of institutional neglect and bias that have left the Indian Muslims far behind other Socio-Religious Communities, in the fields of education, employment, access to credit, and other social and physical infrastructure. The Indian banking sector has evolved over the years in terms of performance and complexity. Despite this development and growth, a large number of people have limited access to the financial services offered by financial institutions. Methods: The concern on which this study is based is the increasing financial exclusion among the Indian population generally and the Muslims in India specifically. In this novel study, we utilized panel data covering 14 Muslim-populated Indian regions (13 states and 1 Union Territory) from 2009 to 2016 to assess the factors influencing financial inclusion in terms of credit and deposit penetration. Results: By employing an explicit econometric model for panel data, it is found that the number of banking offices, per capita net state domestic product, outstanding liabilities, social sector expenditure, number of employees, and interest payments are some of the factors that influence financial inclusion. Conclusion and suggestion: This study will benefit the policymakers, state and government officials, society in general, especially Muslim populations in the relevant areas of Republic of India.